From relationship marketing to total relationship marketing and beyond. Issue 1 (13th February 2017) - Gummesson, Evert
Abstract : Purpose: This paper aims to emphasize the need for generation of more general, abstract and grand theory in marketing by synthesizing relationship marketing and other developments and to address complexity instead of fragmented bits of marketing. Design/methodology/approach: This study is a discourse based on new theoretical developments, literature and personal reflection. Findings: Relationships, networks and interaction constitute the core of marketing. Research limitations/implications: Future focus on theory generation and complexity through case study research and not on fragmented quantitative surveys and hypotheses testing. When complexity is better understood, boil it down to actionable simplicity in the form of mid-range theory. Practical implications: Research in marketing is there to be used in real life; it is not an academic parlor game. The paper addresses complexity instead of shunning it, search for the core of marketing and offer simplification as mid-range theory (checklists, heuristics, etc.) and with focus on decisions, action and results. Originality/value: Going from the current fragmented approach of marketing to a holistic and theory-based approach, linking theory with practice.